Exploring the epidemiology of injuries in athletes of the Olympic Winter Games: A systematic review and meta-analysis - Zang, W.; Fang, M.; Zhang, X.; Xiao, N.; Wang, S.; Mu, L. (Journal of Sports Science & Medicine, 2023)
This study sought to provide a comprehensive assessment of the incidence of sports injuries among athletes participating in the Olympic Winter Games and to investigate contributing factors. We gathered injury data from athletes participating in the recent four Olympic Winter Games, incorporating details on the sports event, sex, injury location, and type. Through a meta-analysis, we calculated the injury incidence rates for each sport and examined the influence of sex and the type of sport on these incidence rates. Out of 11,197 registered athletes, we documented 1,304 sports injuries. The sports events with the highest injury rates were freestyle skiing, snowboarding, alpine skiing, bobsleigh, and ice hockey, with the most frequent injury locations being the knees, thoracic/lumbar/back regions, and the wrist/hand/fingers. Contusions, hematomas, and bruises were the most prevalent injuries, followed by strains (including muscle rupture, tearing, or tendon rupture) and sprains (covering dislocations, subluxations, and ligament ruptures). In the Olympic Winter Games, events such as freestyle skiing, snowboarding, alpine skiing, bobsleigh, and ice hockey pose a particularly high risk. Predominant injury sites include the knee, spine/back, and wrist and hand, with injuries ranging from contusions and hematomas to strains and sprains. For effective injury prevention, it is crucial to emphasize proper medical resource allocation, specialized training for medical personnel, and meticulous venue maintenance.